PENGARUH PUPUK HAYATI MIKORIZA TERHADAP PERTUMBUHAN DAN HASIL TIGA VARIETAS KEDELAI (Glycine max L. Merr): Kata kunci: Kedelai; Pupuk Mikoriza; Varietas - Novia Dwi Isnaini; Sumarmi Sumarmi; Sartono Joko Santosa (Innofarm:Jurnal Inovasi Pertanian, 2022)
The study entitled The Effect of Mycorrhizal Fertilizer on Growth and Yield of Three Soybean Varieties (Glycine max L. Merr) was conducted from December 20, 2021 to March 24, 2022, at the Seed Garden of Food Crops and Horticulture Tohudan, Klipan, Gedongan Village, Colomadu District, Karanganyar Regency. This study aimed to determine the effect of mycorrhizal fertilizer on the growth and yield of three soybean varieties (Glycine max (L.) Merrill). The study used a split plot design (RPT) or a split plot design consisting of 2 treatment factors and 3 replications. The first factor is the variety (V) with 3 levels, namely the Anjasmoro variety (V1), the Argomulyo variety (V2) and the Grobogan variety (V3). grams / polybag (M1), 15 grams / polybag (M2), 22.5 grams / polybag (M3). Parameters observed included plant height (cm), number of leaves (strands), number of pods per plant (fruit), pod weight per plant (g), number of seeds per plant (grain), dry seed weight per plant (g), weight 100 seeds (g). The varietal treatment had an effect on the plant height of the Anjasmoro varieties 52.71 cm high per plant, Argomulyo 50.38 cm planting, and Grobogan 44.63 cm planting. The largest number of Argomulyo leaves was 101.63 leaves per plant, Grobogan 87.08 leaves per plant, and Anjasmoro 68.63 leaves per plant. The number of pods of Anjasmoro was 140.46 per plant, Argomulyo was 126.00 per plant and Grobogan was 90.50 per plant. The number of seeds per plant for Argomulyo was at most 341.42 grains, Anjasmoro was 300.79 grains, and Grobogan was 201.92 grains. Argomulyo seeds weigh 50.62 grams per plant, Grobogan 39.81 grams per plant, and Anjasmoro 34.11 grams per plant. The application of mycorrhizal biofertilizer affects the weight of 100 seeds with a dose of 22.5 grams / polybag on the Grobogan variety weighing 23.97 grams.Keywords : Soybean, Mycorrhizal, Varieties